2020
DOI: 10.3389/fnins.2020.582853
|View full text |Cite
|
Sign up to set email alerts
|

The Way to a Human’s Brain Goes Through Their Stomach: Dietary Factors in Major Depressive Disorder

Abstract: Globally, more than 250 million people are affected by depression (major depressive disorder; MDD), a serious and debilitating mental disorder. Currently available treatment options can have substantial side effects and take weeks to be fully effective. Therefore, it is important to find safe alternatives, which act more rapidly and in a larger number of patients. While much research on MDD focuses on chronic stress as a main risk factor, we here make a point of exploring dietary factors as a somewhat overlook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 263 publications
(314 reference statements)
0
13
0
1
Order By: Relevance
“…In this study, we found that, compared with non-depressed breast cancer patients, depressed patients consumed more carbohydrates and less vitamins (vitamin A, B 2 , B 6 and folic acid), minerals (iron and zinc), and β-carotene, among which vitamin B 2 , iron, and zinc were negatively associated with DepS. It has been suggested that depressed patients often suffer from nutrient deficiencies, including fatty acids, B vitamins, minerals, and amino acids [ 33 ], which might be due to the fact that most depressed patients have unhealthy dietary habits, such as increased sweets and high-fat food intake and decreased vegetables, fruits and fish intake [ 34 ]. Therefore, adherence to a healthy diet might be effective in decreasing the occurrence of DepS in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that, compared with non-depressed breast cancer patients, depressed patients consumed more carbohydrates and less vitamins (vitamin A, B 2 , B 6 and folic acid), minerals (iron and zinc), and β-carotene, among which vitamin B 2 , iron, and zinc were negatively associated with DepS. It has been suggested that depressed patients often suffer from nutrient deficiencies, including fatty acids, B vitamins, minerals, and amino acids [ 33 ], which might be due to the fact that most depressed patients have unhealthy dietary habits, such as increased sweets and high-fat food intake and decreased vegetables, fruits and fish intake [ 34 ]. Therefore, adherence to a healthy diet might be effective in decreasing the occurrence of DepS in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The list is even longer in the case of women, but not men, with depressive symptoms according to recent studies, including also potassium, phosphorus, and copper ( 84 ). All these nutrients are vital for monoamines synthesis, neuroinflammation control, neuroprotection, and the synthesis of growth factors ( 85 ).…”
Section: Nutrition Epigenetics and Mdd: Is There A Link?mentioning
confidence: 99%
“…21 The glucocorticoid receptor (GR) and GC mediate the negative feedback response of the hypothalamus, which involves the regulation of neurogenesis, synaptic plasticity, and hippocampal volume. 22 Excessive secretion of GC reduces the magnitude of the hippocampus of patients and affects their cognition and behavior. 21,23 Furthermore, cognitive ability has a negative correlation with the concentrations of cortisol.…”
Section: Dysregulation Of the Hpa Axismentioning
confidence: 99%